Light-powered swarming phoretic antimony chalcogenide-based microrobots with "on-the-fly" photodegradation abilities - Jancik-Prochazkova, Anna; Pumera, Martin (Nanoscale, 2023)
Microrobots are at the forefront of research for biomedical and environmental applications. Whereas a single microrobot exhibits quite low performance in the large-scale environment, swarms of microrobots are representing a powerful tool in biomedical and environmental applications. Here, we fabricated phoretic Sb2S3-based microrobots that exhibited swarming behavior under light illumination without any addition of chemical fuel. The microrobots were prepared in an environmentally friendly way by reacting the precursors with bio-originated templates in aqueous solution in a microwave reactor. The crystalline Sb2S3 material provided the microrobots with interesting optical and semiconductive properties. Because of the formation of reactive oxygen species (ROS) upon light illumination, the microrobots possessed photocatalytic properties. To demonstrate the photocatalytic abilities, industrially used dyes, quinoline yellow and tartrazine were degraded using microrobots in the "on-the-fly" mode. Overall, this proof-of-concept work showed that Sb2S3 photoactive material is suitable for designing swarming microrobots for environmental remediation applications.